Leisure Time of Jewish Women in late Ottoman Jerusalem - Ben-Naeh, Yaron (MiKAN, 2007)
Various sources reveal a hitherto unknown part of Jewish Sephardi women’s daily life in late Ottoman Jerusalem. A special local feminine leisure culture existed, based on the Harem culture, typical ofupper class Ottoman city denizens, whose main characteristics were female segregation and gender separation. Many, mostly elderly women, lived in Jerusalem, but their lives were ruled by men who wished to maintain the image of a holy community. Free ofthe constant care for their livelihood, Jewish women had much leisure time, which they spent amongst female relatives, neighbors and friends in domestic visits - chatting and singing, sipping coffee, eating sweets and smoking the nargileh. Less often, they ventured outdoors to the bathhouse and for short walks outside the city walls. Communal regulations attempted to regulate these habits. Many of the women’s concerns related to their fate in the next world, therefore they spent much time in prayer, walking to holy cites, and practicing charitable deeds for the poor and needy.